Bounded solutions of one class of nonlinear operator difference equations - Gorodnii, M. F.; Dorogovtsev, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Sufficient conditions for existence of bounded solutions of operator difference equations with quadratic nonlinearity are given.